2021
DOI: 10.21608/jabps.2021.73962.1127
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Molecular Modeling and Biological Evaluation of Novel 1,5-Diarylpyrazole Carboxamide Derivatives as Antiproliferative Agents

Abstract: A series of novel 1,5-diarylpyrazole carboxamide derivatives was designed and synthesized. All the synthesized compounds were biologically evaluated for their in vitro cytotoxic activities against a panel of five cancer cell lines namely, DLD, Hela, K-562, SUIT and HepG-2. The results revealed that compound 5c exhibited the most prominent cytotoxic effect against four tested cell lines with growth inhibition percentages ranged from 75.95 to 123 % and IC50 values of 17.20 and 21.20 μM comparable to that of daun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Moreover, the compounds 5 c and 5 h were evaluated for their effect on the cell cycle in HepG2 cell lines. The stages of cell cycle were detected through flow cytometry after propidium iodide (PI) staining [81] . From the obtained results in Table 3 and Figure 5, it was concluded that 5 c and 5 h caused interruption in the cell cycle progression in the treated HepG2 cells.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Moreover, the compounds 5 c and 5 h were evaluated for their effect on the cell cycle in HepG2 cell lines. The stages of cell cycle were detected through flow cytometry after propidium iodide (PI) staining [81] . From the obtained results in Table 3 and Figure 5, it was concluded that 5 c and 5 h caused interruption in the cell cycle progression in the treated HepG2 cells.…”
Section: Resultsmentioning
confidence: 90%
“…The stages of cell cycle were detected through flow cytometry after propidium iodide (PI) staining. [81] From the obtained results in Table 3 and Figure 5, it was concluded that 5 c and 5 h caused interruption in the cell cycle progression in the treated HepG2 cells. The change in the cell content % was detected in the treated cells with 5 c and 5 h compared to the control cells.…”
Section: Cell Cycle Analysis For 5 C and 5 H By Dna-flow Cytometric A...mentioning
confidence: 81%
See 3 more Smart Citations